Prognostic Implications of the Admission Cardiac Troponin I Levels and Door-to-Balloon Time on Clinical Outcomes in Patients with ST-Segment Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention - Zhao L; Xin M; Piao X; Zhang S; Li Y; Cheng XW (Dove Medical Press, 2022)
Longguo Zhao, Minglong Xin, Xianji Piao, Shengming Zhang, Yanglong Li, Xian Wu Cheng Department of Cardiology and Hypertension, Yanbian University Hospital, Yanji, Jilin, 133000, People's Republic of ChinaCorrespondence: Xian Wu ChengDepartment of Cardiology and Hypertension, Yanbian University Hospital, 1327 Juzijie, Yanji, 133000, People's Republic of ChinaEmail chengxw0908@163.com; xianwu@med.nagoya-u.ac.jpMinglong XinDepartment of Cardiology and Hypertension, Yanbian University Hospital, 1327 Juzijie, Yanji, 133000, People's Republic of ChinaEmail xml.vvv@163.comBackground: The prognostic implications of the admission cTnI level and D2B time combined on in-hospital and 1-year heart failure (HF) and mortality in STEMI patients undergoing a primary percutaneous coronary intervention (PCI) are remain uncertain.Methods and Results: We divided the consecutive 1485 STEMI patients who underwent PCI from January 2015 to October 2019 at our hospital into three groups based on their admission cTnI levels: normal group (< 0.1 ng/mL), middle group (0.1 to less than 3 ng/mL), and high group (≥ 3 ng/mL) and into two groups by their D2B times: > 90 min (> 90-D2B) and ≤ 90 min (≤ 90-D2B). During the in-hospital and 1-year follow-up periods, the incidence of composite clinical events increased significantly with the increase in the admission cTnI level (p < 0.05). In-hospital, the composite rate of death and HF events was significantly higher in the > 90-D2B group compared to the ≤ 90-D2B group (p = 0.006), but its influence disappeared in the 1-year follow-up (p > 0.05). A multivariable logistic analysis revealed that, in the ≤ 90-D2B group, with the exception of the cTnI ≥ 3 ng/mL patients, the cTnI level had no effect on in-hospital or 1-year outcomes; in > 90-D2B group, cTnI ≥ 3ng/mL increased outcomes in both periods.Conclusion: High cTnI levels (≥ 3 ng/mL) on admission are independent of the D2B time for predicting in-hospital and 1-year cardiac events in STEMI patients undergoing PCI.Keywords: cardiac troponin I, acute myocardial infarction, door-to-balloon time, cardiac death, heart failure